2019
DOI: 10.1016/j.ejmp.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Implementing safe and robust Total Marrow Irradiation using Helical Tomotherapy – A practical guide

Abstract: Total Marrow Irradiation (TMI) with Helical Tomotherapy is a radiotherapy treatment technique that targets bone marrow and sanctuary sites prior to stem cell or bone marrow transplantation (SCT/BMT). TMI is a complex procedure that involves several critical steps that all need to be carefully addressed for a successful implementation, such as dose homogeneity in field junctions, choice of target margins, integrity of treatment and backup planning. In this work we present our solution for a robust and reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…Lung D50 achieved in our patients was relatively higher compared to other published series of TMLI [8][9][10]17] and this is possibly due to differences in target delineation, margins and differences in target coverage goals. Varying margins to the chest wall target have been used by investigators which were based either on geometric expansion ranging from 0-10 mm [9,18] or based on chest wall motion [18]. Our coverage goal of 95% of dose to 98% of CTV was higher than the 85% set by others (9) possibly explaining higher lung D50.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lung D50 achieved in our patients was relatively higher compared to other published series of TMLI [8][9][10]17] and this is possibly due to differences in target delineation, margins and differences in target coverage goals. Varying margins to the chest wall target have been used by investigators which were based either on geometric expansion ranging from 0-10 mm [9,18] or based on chest wall motion [18]. Our coverage goal of 95% of dose to 98% of CTV was higher than the 85% set by others (9) possibly explaining higher lung D50.…”
Section: Discussionmentioning
confidence: 93%
“…We have used two sets of CT scans and plans with complementary dose gradient across the junction similar to the one described by Haraldsson, et al [18] for TMI. Planning and optimization processes were similar except that we allowed a lengthier junction to ensure plan robustness.…”
Section: Discussionmentioning
confidence: 99%
“…However, the practice of TBI has witness a steady decline as a result of radiation induced toxicity and alternative use of only chemotherapy based conditioning regimens. Profoundly, several investigators have reported the feasibility of selective irradiation of total marrow (TMI) and lymphatic (TMLI), using volumetric modulated arc therapy (VMAT) and more conveniently with helical tomotherapy (HT) [4][5][6][7]. TMI have shown a signi cant reduction of dose to organs at risk (OAR) as compared to TBI thereby reducing radiation induced toxicity [5,6,8,9] with encouraging complete response rate [9].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment planning of TMI/TMLI using either HT or VMAT is complicated due to extensive and complex irregular shape target volume requiring highly modulated beam intensity, multiple isocenters and eld junctions. HT has been the most preferred high precision treatment modality for TMI/TMLI owing to its ability to treat a maximum length of 135 cm at a time requiring zero or one junction to treat the entire target volume as compared to 4-5 junctions in VMAT [4][5][6][7]. Pre-treatment veri cation of dose delivery in the entire target volume is of paramount importance to ensure accurate delivery of dose to the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation